Optimization and mechanism analysis of a compound additive for unfired bricks made of construction and demolition wastes - Liu, Han-Dong; Fan, Liujun (Frontiers in Materials, 2024)
Construction and demolition waste (CDW) was fully exploited to prepare high-strength and low-cost unfired bricks. A compound additive consisting of sodium silicate, microsilica powder, an early-strength water reducer, and wood fiber was incorporated into the bricks. Tests (compressive tests, freeze-thaw cycle tests, and scanning electron microscopy (SEM)) were carried out to determine the effect of the contents of the additive components on the properties (the strength, softening coefficient, freezing resistance, hydration products, and microscopic morphology) of unfired bricks of different curing ages. The experimental results were used to determine the optimum ratio of the components and the hydration mechanism. The optimized compound additive considerably improved the mechanical properties and crack resistance of the bricks, where the optimum content was found to be only 3.15% of the CDW dry mass. Compared with unfired bricks with no additives, unfired bricks with the optimized compound additive exhibited increases in the 1-and 28-day compressive strengths and softening coefficient of up to 66.8%, 65.9%, and 8.46%, respectively (corresponding to values of 8.46 MPa, 29.36 MPa, and 0.934, respectively) and a decrease in the freeze-thaw strength loss rate of 61.38%. Incorporating the compound additive into the unfired bricks considerably reduced the environmental impact. The SEM micrographs showed that the compound additive increased the silicon-to-calcium ratio and workability of the preparation mixture, increased the hydration rate, promoted the conversion of calcium hydroxide in the product to a C-S-H gel, and enhanced the density and strength of the hydration product.